1993
DOI: 10.1038/ng0493-317
|View full text |Cite
|
Sign up to set email alerts
|

Clustered base substitutions in CTP synthetase conferring drug resistance in Chinese hamster ovary cells

Abstract: Dominantly acting mutations that eliminate the allosteric regulation of CTP synthetase confer a form of multidrug resistance and a mutator phenotype to cultured Chinese hamster ovary cells. Mutations responsible for this phenotype have been identified in 23 independent strains selected for resistance to arabinosyl cytosine and 5-fluorouracil. All these mutations were due to base substitutions at seven sites within a highly conserved region of the ctps gene. This clustering should make it feasible to assess the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 31 publications
3
59
1
Order By: Relevance
“…The black oval indicates the location of the 2-fold crystallographic symmetry axis, which relates subunits of the tightly bound dimer. The previously characterized CTP resistance substitutions are D147E [Chlamydia trachomatis (25)], V*116F, G146E, I148T, M*151I, R158H, and H*229K [hamster (35)], and E155K [hamster (35) and yeast (18)] (an asterisk denotes residues different from those of EcCTPS). Note the potential for substitutions at residues 148 and 151 to disrupt binding at both sites, and the potential for binding at one CTP site to influence binding at the two-fold-related site.…”
Section: Discussionmentioning
confidence: 99%
“…The black oval indicates the location of the 2-fold crystallographic symmetry axis, which relates subunits of the tightly bound dimer. The previously characterized CTP resistance substitutions are D147E [Chlamydia trachomatis (25)], V*116F, G146E, I148T, M*151I, R158H, and H*229K [hamster (35)], and E155K [hamster (35) and yeast (18)] (an asterisk denotes residues different from those of EcCTPS). Note the potential for substitutions at residues 148 and 151 to disrupt binding at both sites, and the potential for binding at one CTP site to influence binding at the two-fold-related site.…”
Section: Discussionmentioning
confidence: 99%
“…Similar CTPS mutations also mediate cancer resistance to cytosine arabinoside and 5-fluorouracil, drugs that do not target this enzyme, by dramatically increasing 1 Abbreviations: CTPS, cytidine triphosphate synthetase; EcCTPS, Escherichia coli cytidine triphosphate synthetase; CPEC, cyclopentenyl cytosine; MAD, multiwavelength anomalous dispersion; TCEP, tricarboxyethyl-phosphine; MPD, 2,4-2-methylpentanediol; DTBS, E. coli dethiobiotin synthetase (BioD) enzyme; CPS, E. coli carbamoyl phosphate synthetase enzyme, CarA subunit; 10 GSA, glutamyl γ-semialdehyde; DAPA, diaminoperlargonic acid; rmsd, root-mean-squared difference in position between atom sets, in angstrom units; ALase, amidoligase reaction, formation of a carbon-nitrogen bond by displacement of a phosphorylated oxygen; GATase, glutamine amidotransferase, refers to the conserved glutamine hydrolysis domain that provides ammonia for a number of diverse reactions. (57,58). These observations suggest that CTPSs are master regulators of CTP levels and that resistance-evading anti-CTPS drugs could be effective therapeutics.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 95%
“…Sequence analysis of the CTP synthetase gene from these mutants has revealed that most of the mutations are clustered within a stretch of 14 amino acids [41]. The most frequent mutations in the clustered region of the enzyme are glutamate-to-lysine and histidine-to-lysine changes [41]. The clustered sites are in a highly conserved region of the CTP synthetases from human cells [42], E. coli [31], Chlamydia trachomatis [43], Bacillus subtilis [44], and S. cerevisiae [4,5].…”
Section: Ctp Regulates Ctp Synthetase Activity and The Synthesis Of Mmentioning
confidence: 99%
“…The mutants were selected for their resistance to the growth inhibitory effects of the chemotherapeutic drugs arabinosyl cytosine and 5-fluorouracil [41]. Sequence analysis of the CTP synthetase gene from these mutants has revealed that most of the mutations are clustered within a stretch of 14 amino acids [41].…”
Section: Ctp Regulates Ctp Synthetase Activity and The Synthesis Of Mmentioning
confidence: 99%
See 1 more Smart Citation